Design A Magnetic Contactless Thruster of Unmanned Underwater Vehicle - Ali, Fara Ashikin; Abdul Azis, Fadilah; Mohd Aras, Mohd Shahrieel; Muhammad Nur , Othman; Shahrum Shah, Abdullah (Praise Worthy Prize, 2013)
This paper describes a design and development of magnetic contactless thruster for Unmanned Underwater Vehicle. The thrusters are one of the most critical underwater technologies that define ROVs overall performance in term of speed. In a non-controllable environment such as sea, the thrusters faced the certain problem such as over pressure, corrosion and shatter. These all will lead leaking to the thrusters. A magnetic contactless of underwater thruster which called TUSHEE thruster is designed to avoid the occurrence of such problems. The CAD software is used as a tool to design these all parts of TUSHEE thruster. The thruster is designed and fabricated into two separate parts which are housed for motor and housing for propeller. Both parts have a plate that holds a magnet. Both plates are printed by using rapid prototyping machine. The rare magnetic material called a Neo magnet with size 2.0 cm for height and 1.3 cm in diameter is used. The 12V Brushless DC motor and 4 blade propeller with 10 cm diameter is chosen for this thruster. PVC is used for both housing with 11.1 cm diameter each. All these materials are chosen based on some criteria such as performance and price. The experimental test is done by the thruster at the swimming pool and laboratory pool. The thruster moves forward with speed 0.214 m/s and the propeller is rotated with 231 RPM. The results from these trials and demonstrations are recorded and shown.